Non-traditional security issues : securitisation of transnational crime in Asia - Laki, James (2009)
Transnational crime involving all forms of domestic crime that tranverse the international boundary with another one or more states have become a concern amongst all peoples of the Asia Pacific region. Although there are many forms of transnational crime this paper focuses on Human and Drug Smuggling, as these have become existential threats affecting many people through out the region.